A phylogenetic study of the South African representatives of the tribe Andropogoneae (Poaceae) - Holder, Francisca (University of the Free State, 2003)
The tribe Andropogoneae makes up half of the grass subfamily Panicoideae, with approximately 85 genera and 960 species (Hartley 1958, Clayton and Renvoize 1986). The genera of the tribe are typically tropical with only a few species extending beyond the tropics into warm temperate regions. From information available it is clear that the African representatives form an integral part of the tribe. In this study we only concentrated on the South African representatives of the tribe. The tribe Andropogoneae has been studied extensively over the last millennium, but there is still an uncertainty about the true basic chromosome number. Previous molecular studies include sequencing of the ndhF, GBSSI and phytochrome B. The morphological variation in the tribe provides an interesting context to examine. This study focused on the sequencing of plastid chloroplast gene trnL-F and nuclear ribosomal DNA the Internal Transcribed Spacer (ITS) to determine the phylogenetic relationships within the tribe. In this study the chromosome numbers of 58 specimens were determined. The genetic chromosome numbers varied with n = 5, 9, 10, 10, 11, 20, 30. For the first time the basic diploid number of n = 5 was observed in the genus Andropogon. Urelythrum aggropyroides was studied for the first time with a somatic chromosome number of 2n = 20. The absence of multivalent and prevalence of bivalents in this study indicate that the genomes of the specimens studied are homologous. This lead us to the conclusion that the tribe consists of allopolyploid species, derived from interspecific hybridization and chromosome doubling. Both the trnL intron and trnL-F intergenic spacer was sequenced. Analysis of the trnL-F gene included 56 accessions and 61 accessions for the ITS gene. Combined analysis of both ITS and trnL-F included 59 accessions. Sequencing data indicated Cymbopogon to be a diploid progenitor of Hyparrhenia and Andropogon of Bothriochloa bladhii. Reticulate evolution was demonstrated in nrITS alleles. ITS and trnL-F data supports the inclusion of Arundinella in Andropogoneae and rejects the subtribal classification of Clayton and Renvoize (1986). This data also does not support the division of the tribe into awned and awnless genera and does not support the “core Andropogoneae” lineage as previously been observed. Most genera in the tribe are polyphyletic, suggesting a much more complex nature for the South African representatives. Molecular data could not prove the basic chromosome number but supported the maturity of the polyploid complex for the South African specimens.

Die tribus Andropogoneae vorm die helfte van die gras subfmilie Panicoidae, met ongeveer 85 genera en 960 spesies (Hartley 1958, Clayton and Renvoize 1986). Die genera in die tribus is gewoonlik tropies, met slegs ‘n paar wat buite die tropiese gebiede na gebiede met ‘n gematigde klimaat versprei het. Die Afrika verteenwoordigers vorm ‘n integrale deel van die tribus. Hierdie studie konsentreer hoofsaaklik op die Suid- Afrikaanse verteenwoordigers van die tribus. Die tribus Andropogoneae is dikwels bestudeer gedurende die laaste millenium, maar daar bestaan nog steeds onsekerheid oor die ware basiese chromosoomgetal van die tribus. Vorige molekulêre studies het die nukleotiedvolgeordebepaling van ndhF, GBSSI, en phytochrome B ingesluit. Die morfologiese variasie in die tribus verskaf ‘n interessante konteks om te bestudeer. Hierdie studie het hoofsaaklik gekonsentreer op die nukleotiedvolgeordebepaling van die chloroplaste gebied trnL-F en die kern ribosomale DNA se intern getranskribeerde streke (ITS), om die filogenetiese verwantskappe binne die tribus vas te stel. Tydens hierdie studie is die chromosoomgetalle van 58 eksemplare bepaal. Die gametiese chromosoomgetalle het gewissel tussen n = 5, 9, 10, 11, 20, 30. Die basiese diploïede getal van n = 5 is vir die eerste keer in die genus Andropogon waargeneem. Urelythrum aggropyroides is vir die eerste keer betudeer, met ‘n somatiese chromosoom getal van 2n = 20. Die afwesigheid van multivalente en die teenwoordigheid van bivalente in hierdie studie is ‘n aanduiding dat die genome van die spesies in die studie homeologies is. Dit dui daarop dat die tribus bestaan uit allopoliploïede spesies, wat afgelei is vanaf interspesifieke verbastering en chromosoomverdubbeling. Beide die trnL intron en die trnL-F intergeniese streek se nukleotiedvolgorde is bepaal. Analises van die trnL-F geen het 56 eksemplare ingesluit terwyl 61 eksemplare vir ITS volgorde bepaling gebruik is. ‘n Gekombineerde analise van beide ITS en trnL-F het 59 eksemplare ingesluit. Nukleotiedvolgordebepaling dui aan dat die genus Cymbopogon ‘n diploïede voorganger van Hyparrhenia is en Andropogon van Bothriochloa bladhii. Retikulerende evolusie kom voor in die nrITS allele. ITS en trnL-F data ondersteun die insluiting van Arundinella in die tribus Andropogoneae en verwerp die subtribus klassifikasie van Clayton en Renvoize (1986). Hierdie data ondersteun ook nie die verdeling van die tribus in geangelde en angellose genera en verder ondersteun dit ook nie die suiwer basiese Andropogoneae groepering soos in vorige studies waargeneem nie. Die meeste genera in die tribus is polifeleties, wat ‘n baie meer komplekse samestelling vir die Suid-Afrikaanse verteenwoorigers van die tribus voorstel. Molekulêre data het nie bewyse gelewer vir die ware basiese chromosoomgetal nie maar het wel die volwasse aard van die poliploïede kompleks vir die Suid- Afrikaanse spesies ondersteun.
Thesis (Ph.D. (Plant Sciences: Genetics))--University of the Free State, 2003
Keywords: Poaceae; Panicoideae; Andropogoneae; Ccytogenetics; Polyploidy; Allopolyploidy; DNA sequencing; trnL-F; Internal transcribed spacer (ITS); Reticulate evolution; Grasses -- South Africa; Grasses -- Classification; Grasses -- Phylogeny; Cladistic analysis